2020
DOI: 10.1108/ec-05-2019-0197
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic-viscoplastic combined constitutive model for glassy amorphous polymers under loading/unloading/no-load states

Abstract: Purpose This study aims to propose a novel viscoelastic–viscoplastic combined constitutive model for glassy amorphous polymers within the framework of thermodynamics at finite strain that is capable of capturing their rate-dependent inelastic mechanical behavior in wide ranges of deformation rate and amount. Design/methodology/approach The rheology model whose viscoelastic and viscoplastic elements are connected in series is set in accordance with the multi-mechanism theory. Then, the constitutive functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…As a novel modeling approach, the fractional order derivative model has attracted great interest due to its simple form and more flexible description of various physical phenomena 29 including anomalous diffusion, 30 biomedical engineering, 10 and control system, 31 especially in the field of viscoelastic mechanics 32 where the mechanical property of described materials can be revealed by the index of fractional order 33 . Recently, the variable‐order fractional operator has been established, enables the fractional order to be functions of independent state variables, such as time 34 and temperature, 35 existing excellent applications in rheology, 36,37 mechanics 38,39 and chaotic systems 40 . However, a difficulty of the above method lies in how to appropriately define the suitable variable‐order function which is not only able to meet the requirement of fractional modeling but also the subsequent mathematical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As a novel modeling approach, the fractional order derivative model has attracted great interest due to its simple form and more flexible description of various physical phenomena 29 including anomalous diffusion, 30 biomedical engineering, 10 and control system, 31 especially in the field of viscoelastic mechanics 32 where the mechanical property of described materials can be revealed by the index of fractional order 33 . Recently, the variable‐order fractional operator has been established, enables the fractional order to be functions of independent state variables, such as time 34 and temperature, 35 existing excellent applications in rheology, 36,37 mechanics 38,39 and chaotic systems 40 . However, a difficulty of the above method lies in how to appropriately define the suitable variable‐order function which is not only able to meet the requirement of fractional modeling but also the subsequent mathematical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistency between the observation of Colak et al [21] on the one hand and Nikoukalam and Sideri [20], on the other hand can be related to the influence of the applied cyclic deformation magnitude and number of loading cycles. Recent research regarding the modelling of the cyclic response of polymers can be found in several references [22][23][24][25][26][27][28][29]. A coupled hyperelastic-viscoplastic model in Shojaei and Volgers [23] and a parallel elastic-viscoplastic network model in Qi et al [27] shows capability for the investigation of a highly-crystalline and semi-crystalline polymers, respectively.…”
mentioning
confidence: 99%